1996
DOI: 10.1177/074193259601700402
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Management in Inclusive Classrooms

Abstract: PERHAPS THE PRIMARY REQUISITE FOR STUDENTS WHO ENTER INCLUSIVE SETTINGS IS THE ABILITY OF THE STUDENTS AND TEACHERS TO EFFECTIVELY DEAL WITH BEHAVIOR ISSUES. THE PURPOSE OF THIS ARTICLE IS TO DESCRIBE (A) COMPONENTS OF EFFECTIVE BEHAVIOR MANAGEMENT PROGRAMS AND (B) HOW ONE TEACHER, FACED WITH A VARIETY OF STUDENT BEHAVIORS, WAS ABLE TO VIEW THE CONTEXT OF HER SITUATION, EVALUATE BOTH TEACHER AND STUDENT BEHAVIORS, AND BRING ABOUT DRAMATIC CHANGES IN HER CLASSROOM. DISCUSSION INCLUDES PROACTIVE METHODS TEACHERS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Noting that many students with special needs seem to require direct instruction of appropriate behaviors, some researchers (Carpenter & McKee-Higgins, 1996;Colvin, Kameenui, & Sugai, 1993) suggested what they term an instructional approach to behavior management. In this approach, the focus is on directly instructing students in appropriate behaviors and responses to classroom situations and activities.…”
Section: The Inclusion Contextmentioning
confidence: 99%
“…Noting that many students with special needs seem to require direct instruction of appropriate behaviors, some researchers (Carpenter & McKee-Higgins, 1996;Colvin, Kameenui, & Sugai, 1993) suggested what they term an instructional approach to behavior management. In this approach, the focus is on directly instructing students in appropriate behaviors and responses to classroom situations and activities.…”
Section: The Inclusion Contextmentioning
confidence: 99%
“…Carpenter and McKee-Higgins ( 1996) cited research that has shown that one of the essential components for the creation of a positive class climate is a high rate of student academic involvement and achievement in which the content of the curriculum and instructional delivery focus on high rates of student engagement during instruction and practice.…”
Section: Focus0flmentioning
confidence: 99%
“…This high degree of time-on-task and appropriate instructional strategies may represent an additional means of decreasing disruptive behavior in the classroom and may promote gains in academic performance of students. Carpenter and McKee-Higgins ( 1996) cited research that has shown that one of the essential components for the creation of a positive class climate is a high rate of student academic involvement and achievement in which the content of the curriculum and instructional delivery focus on high rates of student engagement during instruction and practice.…”
Section: Focus0flmentioning
confidence: 99%
“…Consistent behavior helps as changing or shifting strategies show a lack of decisiveness when misbehavior occurs. Keeping students occupied is one way to handle behavioral problem as busy students are far less likely to exhibit disruptive behavior [4]. The students should work at appropriate levels; boredom and frustration often lead to students' acting out [10].…”
Section: Positive Classroom Behaviormentioning
confidence: 99%